Health And Politics In The Covid-19 Crisis From A New Testament Hermeneutical Perspective - Lampe, Peter (Acta theologica, 2020)
Against the backdrop of the COVID-19 crisis and on the basis of New Testament text examples (Mark 3:1-6; 2:23-28; 1 Cor. 8), the article reflects the relationships between health/healing and eschatology, theology of creation, law, and politics. It is argued that the experience of the global crisis of 2020 is forcing the global community to reconsider its modes of living, with alternative visions required. New Testament hermeneutics can contribute impulses to the global and crosscultural discourse about change regarding, for example, the perception of health and healing, the ethics of human kindness, the design and application of laws, the limits of freedom, the role of the notion of “God”, and the First Commandment in secular societies or the role of often absolutised principles such as maximisation of profit and efficiency.